-6p-2(4-6p)=3(p-2)-26

Simple and best practice solution for -6p-2(4-6p)=3(p-2)-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6p-2(4-6p)=3(p-2)-26 equation:


Simplifying
-6p + -2(4 + -6p) = 3(p + -2) + -26
-6p + (4 * -2 + -6p * -2) = 3(p + -2) + -26
-6p + (-8 + 12p) = 3(p + -2) + -26

Reorder the terms:
-8 + -6p + 12p = 3(p + -2) + -26

Combine like terms: -6p + 12p = 6p
-8 + 6p = 3(p + -2) + -26

Reorder the terms:
-8 + 6p = 3(-2 + p) + -26
-8 + 6p = (-2 * 3 + p * 3) + -26
-8 + 6p = (-6 + 3p) + -26

Reorder the terms:
-8 + 6p = -6 + -26 + 3p

Combine like terms: -6 + -26 = -32
-8 + 6p = -32 + 3p

Solving
-8 + 6p = -32 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
-8 + 6p + -3p = -32 + 3p + -3p

Combine like terms: 6p + -3p = 3p
-8 + 3p = -32 + 3p + -3p

Combine like terms: 3p + -3p = 0
-8 + 3p = -32 + 0
-8 + 3p = -32

Add '8' to each side of the equation.
-8 + 8 + 3p = -32 + 8

Combine like terms: -8 + 8 = 0
0 + 3p = -32 + 8
3p = -32 + 8

Combine like terms: -32 + 8 = -24
3p = -24

Divide each side by '3'.
p = -8

Simplifying
p = -8

See similar equations:

| -4x+6+2(x+5)=-2(x+4) | | -5(4+m)+2=m | | -5(4+m)+2=-3.6 | | 2x*ln(x)+x= | | 1.39x=8.34 | | -5(4+m)+2= | | m-3.75=12.25 | | lnx+ln(x+2)=-1 | | 15x^2-21=0 | | 8x=7-3y9y=-20x+13 | | 15s+22=7m+18 | | (9w-x)(9w-x)= | | w-18=14 | | x^2+2x+e=0 | | 6(8)-2(b)=50 | | (7v-4w)(7v-4w)= | | 2(8)+b=25 | | -3=9x-2 | | 6(5)-2(b)=50 | | 81=36+6x | | 22x-9-16x+4=18x-7-12x+14 | | 2(5)+b=25 | | 49=3w+10 | | -2-5x=2x+12 | | x^2-x-t-5= | | -4x+6+2(x-5)=-2(x+4) | | (3a-3)(a+5)= | | 4y+9-2=0 | | 38.79+4x=110 | | X^2+14x-63=0 | | 4+2x=5x+7-4x | | 2(4y^2-11y+8)=0 |

Equations solver categories